What factors are barriers and enablers to implementing differentiated mathematics instruction in elementary schools? - Indrawati, Delia; Habibie, Ramadhan Kurnia; Budiyono; Zuhdi, Ulhaq (Elementary Teacher Education Program, Majalengka University, 2024)
Differentiated instruction is a pedagogical approach designed to address diverse student needs, yet its implementation in primary school mathematics remains challenging. This study investigates the barriers and enablers in applying differentiated mathematics instruction, providing insights into practical challenges and strategies for success. Using a qualitative case study design, data were collected through in-depth interviews, classroom observations, and document analysis in five primary schools, involving students, teachers, and school principals selected through purposive sampling. The findings reveal that the primary barriers include limited teacher training on differentiation strategies, time constraints in lesson planning, and inadequate support systems, such as resources and collaboration opportunities. On the other hand, key enablers include strong leadership support, flexible teaching materials, and professional learning communities that foster peer knowledge sharing. The study highlights the interplay between institutional support and teacher agency as critical for successful implementation. Its novelty lies in offering actionable recommendations, such as incorporating differentiation-focused training into professional development and promoting collaborative educator networks. These findings contribute to the discourse on differentiated instruction, offering practical strategies and systemic changes to enhance equity and engagement in primary mathematics education.